2010
DOI: 10.1073/pnas.1003540107
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study (GWAS)-identified disease risk alleles do not compromise human longevity

Abstract: A set of currently known alleles increasing the risk for coronary artery disease, cancer, and type 2 diabetes as identified by genomewide association studies was tested for compatibility with human longevity. Here, we show that nonagenarian siblings from longlived families and singletons older than 85 y of age from the general population carry the same number of disease risk alleles as young controls. Longevity in this study population is not compromised by the cumulative effect of this set of risk alleles for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
119
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 32 publications
9
119
3
2
Order By: Relevance
“…To explain this finding, the authors assume that the risk alleles included in the analyses were mainly related to beta cell function, whereas the better glucose metabolism in the offspring was due to better insulin sensitivity. Alternatively, further results from the Leiden Longevity Study suggest that alleles protecting from disease rather than risk alleles may determine longevity [14]: long-lived individuals and younger controls did not differ in the number of risk alleles associated with cardiovascular disease, cancer and diabetes, and protective alleles may have a stronger effect on longevity than cumulated risk alleles.…”
Section: Discussionmentioning
confidence: 99%
“…To explain this finding, the authors assume that the risk alleles included in the analyses were mainly related to beta cell function, whereas the better glucose metabolism in the offspring was due to better insulin sensitivity. Alternatively, further results from the Leiden Longevity Study suggest that alleles protecting from disease rather than risk alleles may determine longevity [14]: long-lived individuals and younger controls did not differ in the number of risk alleles associated with cardiovascular disease, cancer and diabetes, and protective alleles may have a stronger effect on longevity than cumulated risk alleles.…”
Section: Discussionmentioning
confidence: 99%
“…As extreme longevity appears to be a result of genetic factors more than environmental ones, when compared to an average lifespan, significant effort has gone into determining which genetic variants can slow aging and diminish the risk for age‐related diseases. Interestingly, the Leiden Longevity Study showed that, by GWAS, genomes of nonagenarians carry the same number of disease risk alleles for coronary artery disease, cancer and type 2 diabetes as young controls (Beekman et al ., 2010). These results hint toward the perception that these long‐lived individuals could carry “protective genes” that may work in general cellular defense mechanisms, for example, against oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Even more disappointing result is that some genes predisposing to geriatric diseases discovered by GWAS appear to be not correlated with human longevity (Beekman et al 2010;Deelen et al 2011). This result questions whether findings obtained from GWAS may provide insights into the bio-genetic mechanisms underlying a healthy lifespan.…”
Section: Introductionmentioning
confidence: 99%
“…The other approach focuses on genetics of individuals with exceptionally long life Melzer et al 2007;De Benedictis et al 2001;Willcox et al 2008a). Despite notable progress of these approaches (Salvioli et al 2006;Christensen et al 2006;Teslovich et al 2010;Barzilai et al 2003;Koropatnick et al 2008;Willcox et al 2008a;Flachsbart et al 2009;Sebastiani et al 2010;Ku et al 2010;Bloss et al 2011), unraveling the role of genes in regulating health and lifespan and, consequently, potential of these factors for effective interventional strategies is still very limited (Manolio et al 2008;Cutler and Mattson 2006;McClellan and King 2010;Gibson 2009;Goldstein 2009;Plomin et al 2009;Gorlov et al 2008;Lunetta et al 2007;Newman et al 2010;Beekman et al 2010) explaining only a small fraction of genetic susceptibility (Frazer et al 2009;Kraja et al 2011). For instance, combined associations of 13 SNPs with blood pressure (BP) revealed by the CHARGE (Levy et al 2009) and Global BPgen (Newton-Cheh et al 2009) consortia explained less than 2% of the BP variance (Kraja et al 2011).…”
Section: Introductionmentioning
confidence: 99%